Restoring the commons: a gendered analysis of customary water tenure in Sub-Saharan Africa - van Koppen, Barbara (Ubiquity Press, Ltd., 2023)
Customary water tenure in low-and middle-income rural areas has received limited academic, policy, and legal attention as yet. This paper seeks to conceptualize and analyse gender-differentiated living customary water tenure, focusing on sub-Saharan Africa. Extensive literature review suggests four gendered domains: first, water needs and uses; second, strategies to meet those needs by directly accessing water sources, and, with increasing wealth by investing individually or collectively in water infrastructure for self-supply, creating infrastructure-related ‘commons’ in the case of collective systems; third, at community scale, the ‘sharing in’ of communities’ naturally available water resources that flow into infrastructure; and, fourth, ‘sharing out’ of those resources with neighbouring communities but also powerful third parties of foreign and national high impact users. Rendering the gendered community more visible as the main agent to manage its water resources as the commons provides evidence for a range of policies, laws and interventions, including gender equitable and community-led water infrastructure development integrating domestic and productive spheres; strengthening customary arrangements to share water resources as a commons within a community or with neighbouring communities, and the long overdue formal protection of customary water tenure against ‘water grabs’ by powerful third parties.